A rare cause of heart failure: aortocaval fistula associated with herniated lumbar disc surgery - Aksüyek Savaş Çelebi; Alper Tosya; Barış Uymaz; Kenan Ömürlü; Tayfun Aybek (KARE Publishing, 2014)
Although aortocaval fistula is mostly encountered as a complication of abdominal aortic aneurysms, it may also arise as a complication of lumbar disc surgery. Great arteriovenous shunts especially may lead to high-output heart failure in due time. In this paper, we aim to present a case of high-output heart failure secondary to aortocaval fistule caused by lumbar disc surgery.